2004
DOI: 10.1080/09637480400002990
|View full text |Cite
|
Sign up to set email alerts
|

Fat and sodium chloride reduction in sausages using κ-carrageenan and other salts

Abstract: Fat and sodium chloride were reduced in a sausage formulation including kappa-carrageenan and other salts, as potassium and calcium chloride, in different concentrations, in order to compensate the ionic strength during myofibrillar protein extraction and solubilisation, and to promote the carrageenan stable conformation and gelation. Four different treatments were employed reducing fat from 15 to 10% and sodium chloride from 2.5 to 1.5% and 1%. Potassium chloride was added at 0.5% to all the treatments, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Gel strength of salt-soluble beef protein was the strongest after addition of potassium chloride, followed by sodium chloride, and then calcium chloride (Sun & Holley, 2010). Also Totosaus, Alfaro-Rodriguez, and Pérez-Chabela (2004) informed that κ-carrageenan addition improved quality and sensorial parameters of low-fat meat products due to the incorporation of K + or Ca 2+ which stabilize the carrageenan molecules. On the other hand, partially sodiumreplaced formulations without TPP (4, 5, and 6) were less elastic than samples containing TPP (0, 1, 7, 8 and 9) indicating the TPP importance in gel structure development.…”
Section: Regression Coefficientsmentioning
confidence: 93%
See 3 more Smart Citations
“…Gel strength of salt-soluble beef protein was the strongest after addition of potassium chloride, followed by sodium chloride, and then calcium chloride (Sun & Holley, 2010). Also Totosaus, Alfaro-Rodriguez, and Pérez-Chabela (2004) informed that κ-carrageenan addition improved quality and sensorial parameters of low-fat meat products due to the incorporation of K + or Ca 2+ which stabilize the carrageenan molecules. On the other hand, partially sodiumreplaced formulations without TPP (4, 5, and 6) were less elastic than samples containing TPP (0, 1, 7, 8 and 9) indicating the TPP importance in gel structure development.…”
Section: Regression Coefficientsmentioning
confidence: 93%
“…Other authors have reported similar results consistent with this work. Totosaus et al (2004) informed that the NaCl partial replacement by other salts (KCl or CaCl 2 ) did not negatively affect process yield or water retention capacity of low fat sausages. Moreover Trius, Sebranek, Rust, and Carr (1994) reported a process yield increase in meat system when KCl was used as substitute of NaCl.…”
Section: Effect Of Nacl Partial Replacement On Quality Parametersmentioning
confidence: 98%
See 2 more Smart Citations
“…This formulation was employed since the reduced fat level and the sodium, potassium, and calcium chloride concentrations resulted in no differences in instrumental and sensorial texture, besides no detrimental effect on cooking losses or fat release. [14] The former formulation was employed to determine if the performance of TLAB can be the same in a fat and sodium reduced/added water meat batter. Ingredients and formulations are listed in Table 1.…”
Section: Sausage Formulation and Lactic Acid Bacteria Inoculationmentioning
confidence: 99%